Long-term treatment with galcanezumab in patients with chronic migraine: results from the open-label extension of the REGAIN study - Pozo-Rosich, Patricia; Detke, Holland C.; Wang, Shufang; Doležil, David; Li, Lily Q.; Aurora, Sheena K.; Reuter, Uwe (Current medical research and opinion, 2022)
Galcanezumab, a monoclonal antibody to calcitonin gene-related peptide, was found to be safe and efficacious for the preventive treatment of chronic migraine based on the randomized, placebo-controlled double-blind period of the REGAIN study. Long-term safety and efficacy were assessed in an open-label extension. Patients 18-65 years old with chronic migraine completing the 3-month double-blind period of REGAIN could enter a 9-month open-label extension (OLE; months 4-12). Upon entering the OLE, patients received a 240-mg galcanezumab loading dose, then 120 mg at the next month, with flexible dosing thereafter (120 or 240 mg/month). The primary efficacy measure was the mean change in the number of monthly migraine headache days from double-blind baseline to month 12. Other endpoints included response rates (based on percent reduction in monthly migraine headache days from double-blind baseline to month 12), safety and tolerability. Of patients who completed double-blind treatment, 1022 (99%) entered the OLE, with 81% completing month 12. From a baseline of 19.4 monthly migraine headache days at the beginning of the double-blind period, patients at month 12 in the previous placebo, 120-mg, and 240-mg galcanezumab groups had a mean change of −8.5, −9.0, and −8.0, respectively (SE = 0.43 to 0.55, within-group p's < .001). At month 12, the percentage of patients with ≥50% response was 57%, 57%, and 53%, respectively. Percentage with ≥75% response was 32%, 31%, and 30%, respectively. Percentage with 100% response was 8%, 6%, and 6%, respectively. There were no significant new safety findings during the open-label period. The incidence of discontinuation from the OLE due to adverse events was 5%. Galcanezumab was effective, safe, and well-tolerated, with high adherence, for up to 12 months of treatment in patients with chronic migraine. Clinicaltrials.gov identifier: NCT02614261; www.clinicaltrials.gov/ct2/show/NCT02614261